Attitudes of special education teachers towards sexuality of male students with intellectual disability in Keramat, Kuala Lumpur/ Siti Nurul Ain Saari and Padma A. Rahman - Saari, Siti Nurul Ain; A. Rahman, Padma (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Positive attitudes of professionals towards the sexuality of male students with intellectual disability (ID) are crucial to promote their healthy sexual development and their sexual rights. Special education teachers are one of the professionals working in close proximity to the students with ID and plays big role in delivering sexuality education to these students. This study aims to examine the attitude of special education teachers towards the sexuality of male students with ID and to identify any relationship between the attitudes of special education teachers towards the sexuality of male students with ID and their demographic characteristics. Cross-sectional quantitative study design with purposive sampling were utilized. Attitudes to Sexuality Questionnaire: Individuals with an ID (ASQ-ID) were distributed to 114 special education teachers in 13 primary and secondary schools in Keramat, Kuala Lumpur. It was found that the special education teachers have positive views towards the sexuality of male students with ID. There is relationship found between attitudes and the age of special education teachers. Future research should consider increasing the sample size and include participants from both rural and urban locations.